The Effect of Axial Loading on Ulnar Variance - Ozer, Kagan; Zhu, Andy F.; Siljander, Breana; Lawton, Jeffrey N.; Waljee, Jennifer F. (Journal of Wrist Surgery, 2018)
Background Forearm rotation results in change in ulnar variance. Axial loading of the wrist is required to maintain daily activities. Change in ulnar variance during axial loading has not been investigated previously.Purpose To measure the change in ulnar variance on axially loaded wrists.Patients and Methods We examined 21 asymptomatic individuals and 24 patients with unilateral ulnar-sided wrist pain. All patients underwent standard neutral posteroanterior wrist radiographs without load and under axial loading on bilateral wrists. Axial loading was standardized at 18.1 kgf using an analog weight scale. A magnetic resonance (MR) arthrogram was obtained only in patients with ulnar-sided wrist pain. Beighton flexibility score was recorded on healthy volunteers. Change in ulnar variance between 0 and 18.1 kgf was compared for each wrist among all subjects. A correlation was sought between the change in ulnar variance, MR arthrogram findings, and physical examination.Results In individuals without wrist pain, on average, 0.4 mm increase in ulnar variance was measured between 0 and 18.1 kgf. There was no difference between the dominant and nondominant side. No correlation was found with increasing age. In contrast, patients with ulnar-sided wrist pain displayed an average increase of 0.8 mm in ulnar variance. Compared with the contralateral wrist, more than 1 mm increase in ulnar variance was correlated with intra-articular pathologies including dorsoulnar ligament disruption, central triangular fibrocartilage complex (TFCC) perforation, and foveal detachment.Conclusion Compared with contralateral side, more than 1 mm increase in ulnar variance is suggestive of longitudinal instability or TFCC pathology.Level of Evidence Level II, diagnostic.
Keywords: ulnocarpal abutment; impingement; ulnar variance; TFCC; axial loading